Identifying Patterns of Inconsistency in Parenting Practices and Their Interpretations by Adolescents: A Narrative Inquiry - Oliveira, Mariana; Sánchez, Carmen (Applied Family Therapy Journal (AFTJ), 2025)
Objective: The objective of this study was to explore how adolescents perceive and interpret patterns of inconsistency in parenting practices and the implications of these interpretations for their emotional and behavioral adjustment. Methods and Materials: This qualitative research employed a narrative inquiry design to capture adolescents’ lived experiences of inconsistent parenting. Twenty-two adolescents from Spain, aged 14 to 18 years, participated in semi-structured interviews that focused on parental communication, discipline, and emotional support. Participants were selected through purposive sampling to ensure diversity in gender, family structure, and socioeconomic background. Interviews lasted between 45 and 60 minutes, were audio-recorded with informed consent, and transcribed verbatim. Data collection continued until theoretical saturation was reached. Transcripts were coded and analyzed thematically using NVivo 14 software, following open coding, categorization, and constant comparison to identify recurring themes and patterns. Findings: Analysis revealed four main themes: inconsistent communication, contradictory discipline practices, unstable emotional climate, and adolescent interpretations and coping strategies. Subthemes included mixed parental messages, unequal rule enforcement, conditional affection, and coping mechanisms such as rationalization, distancing, rebellion, and meaning-making. Adolescents reported that inconsistent parenting created confusion, insecurity, and tension but also described strategies to reinterpret or resist such practices. These narratives align with prior studies linking inconsistent parenting to both internalizing and externalizing symptoms, while also highlighting adolescents’ agency in constructing meaning from their experiences. Conclusion: The study underscores the significance of consistency in parental communication, discipline, and emotional availability for adolescent well-being. Adolescents actively interpret and cope with inconsistencies, which shapes their developmental trajectories. Narrative inquiry provides valuable insights into these processes, suggesting the need for interventions that promote mindful, predictable parenting and supportive environments that strengthen adolescent resilience.